El nitrogeno - Rodriguez Esquivel,Douglas; Flores Barbosa, Elsa; Lopez Bravo, Donald; Muñoz Groá, Juan; Martinez, Martin; Ordeñana Obando, Wilfredo; Padilla Morales, Almicar; Ramirez Palma, Obed; Sandoval Herrara, Ligia; Zelaya Castro, Rodolfo; Acuña Espinal, Efrain (Managua (Nicaragua), 1996)
(Es)
Ilus.; 10 ref.